The Relationship between Education Levels with Knowledge, Attitudes, and Practice in Hypertension Patients - Nimas Citra Nur Baety; Sri Rahayu (GLOBAL HEALTH SCIENCE GROUP, 2024)
Hypertension is called a “silent killer”, many hypertension sufferers do not realize that they have hypertension because hypertension is often asymptomatic so, hypertension sufferers only realize that they have hypertension after they experience complications. This study focuses on examining the relationship between education level with the knowledge, attitudes, and practices of hypertension patients. This study uses quantitative research, with the research design using a cross-sectional study. The sampling technique used is a purposive sampling technique. The samples taken were 100 samples of hypertension patients at dr. Soeratno Sragen Regional Hospital. The research instrument used the knowledge, attitude, practice (KAP) questionnaire. The results of the study showed that there was a relationship between the level of education with the knowledge and attitudes of hypertensive patients, each of which produced a p-value = 0.029 <0.05 and p-value = 0.002 <0.05. The results of the next study, namely the level of education with the behavior of hypertensive patients, showed no significant relationship with p-value = 0.459> 0.05. The higher the level of education affects a person's knowledge and attitude, the better the level of education, the better the level of knowledge and attitude. While from the statistical test between the level of education and practice, there is no relationship between the two, this shows that someone with a high level of education does not necessarily have a good practice. Practice can be formed from many factors, not only from the level of education.